1998
DOI: 10.1191/135245898678909538
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte activation in multiple sclerosis

Abstract: Monocytes, macrophages, and microglia have a central role in the CNS inflammation of MS. Monocytes are important in the earliest events in MS. Peripheral blood monocytes secrete prostaglandins before MS attacks. During clinical activity monocyte activation markers increase and IL-1 and TNF-alpha levels are elevated. Other monocyte products such as IL-10 reduce inflammation. IL-10 mRNA in MNC is increased during stable disease. Manipulation of monokine secretion and expression of monocyte surface proteins are r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
9
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…Finally, although the age ranges of the healthy subjects and MS patients were similar, the means were significantly different as well as the female:male ratio. However, even with these differences, our findings are in line with previous studies comparing total monocyte phenotypes and responses in healthy and MS populations 3 , 11 , 12 . Furthermore, we found no significant correlation between age and cytokine production, suggesting that a difference in age was not responsible for the effects we observed ().…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Finally, although the age ranges of the healthy subjects and MS patients were similar, the means were significantly different as well as the female:male ratio. However, even with these differences, our findings are in line with previous studies comparing total monocyte phenotypes and responses in healthy and MS populations 3 , 11 , 12 . Furthermore, we found no significant correlation between age and cytokine production, suggesting that a difference in age was not responsible for the effects we observed ().…”
Section: Discussionsupporting
confidence: 91%
“…Immune cells have an important role in the pathogenesis of MS, and among them, monocytes and T cells are known as promoters of inflammation during MS 1 , 2 . Previous research has shown that the circulating monocytes of MS patients have characteristics of classically activated monocytes, including the upregulated expression of CD40, CD86, HLA‐DR 3 and inflammatory cytokines, such as interleukin (IL)‐12. The upregulation of these activation markers and cytokines leads to the stimulation and sustained activation of inflammatory T helper type1 (Th1) and Th17 cells, which are key drivers of inflammation during MS 4 , 5 , 6 …”
mentioning
confidence: 99%
“…Significant differences in full blood count parameters from the MS cohort were observed, and consistent with previous literature on female MS patients, ESR results were significantly increased compared to CFS/ME and non‐fatigued controls . This result suggests that there is significant peripheral inflammation in this cohort of untreated patients with MS. Additional significant increases were reported for lymphocyte and monocyte results in the MS cohort compared to CFS/ME and the non‐fatigued controls; however, previous literature has reported no significant differences . The small sample size may contribute to differences observed in white blood cell parameters in this MS cohort.…”
Section: Discussionmentioning
confidence: 56%
“…Thus, it is possible that levels of secretion contributed by a minor cell population, such as monocytes of MS patients, are too low to be detected. The expression of TWEAK at the monocyte cell surface could represent a marker of monocyte activation, which has been correlated previously with MS disease activity [18,19], and histological studies in MS brain material clearly suggested that infiltration of activated monocytes plays an important role in lesion formation [20]. Filion et al [21] showed that monocytes of MS patients produced increased levels of soluble proinflammatory cytokine such as IL-1␤, IL-6, and TNF-␣.…”
mentioning
confidence: 62%